2015
DOI: 10.1038/cr.2015.143
|View full text |Cite
|
Sign up to set email alerts
|

Genetic lineage tracing identifies in situ Kit-expressing cardiomyocytes

Abstract: Cardiac cells marked by c-Kit or Kit, dubbed cardiac stem cells (CSCs), are in clinical trials to investigate their ability to stimulate cardiac regeneration and repair. These studies were initially motivated by the purported cardiogenic activity of these cells. Recent lineage tracing studies using Kit promoter to drive expression of the inducible Cre recombinase showed that these CSCs had highly limited cardiogenic activity, inadequate to support efficient cardiac repair. Here we reassess the lineage tracing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
142
2
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(153 citation statements)
references
References 25 publications
(43 reference statements)
5
142
2
4
Order By: Relevance
“…Attempting to shed light on these issues, Cai and Zhou and colleagues recently reported the generation of more sensitive knock-in alleles inserting conditional CRE and/or marker cassettes directly into the ATG start codon of the first Kit coding exon (Liu et al, 2016;Sultana et al, 2015). With these tools, in contrast to previous studies, KIT + cells were found to be abundant in fetal hearts and throughout postnatal life into adulthood.…”
Section: In Vivo Lineage Descendantsmentioning
confidence: 62%
See 1 more Smart Citation
“…Attempting to shed light on these issues, Cai and Zhou and colleagues recently reported the generation of more sensitive knock-in alleles inserting conditional CRE and/or marker cassettes directly into the ATG start codon of the first Kit coding exon (Liu et al, 2016;Sultana et al, 2015). With these tools, in contrast to previous studies, KIT + cells were found to be abundant in fetal hearts and throughout postnatal life into adulthood.…”
Section: In Vivo Lineage Descendantsmentioning
confidence: 62%
“…They maintained their endothelial identity after myocardial infarction and, consistent with the van Berlo et al study discussed above, only very rare cells were identified in healthy or injured hearts that coexpressed KIT and a marker of cardiomyocyte precursors (NKX2-5) or differentiated cardiomyocytes (troponin T). With these new lineage tools, some cardiomyocytes could be labeled immediately after lineage tracing, suggesting that those traced in the adult heart did not derive from myocardial stem cells (Liu et al, 2016). These studies claim to have revealed the identity and behavior of the majority population of KIT + cells within the heart, most of which were not detected previously owing to the insensitivity of antibodies and lineage-tracing strategies.…”
Section: In Vivo Lineage Descendantsmentioning
confidence: 86%
“…One may ask whether cardiac stem cells such as Kit + cells, Sca1 + cells, or epicardial progenitors contribute to new coronary endothelial cells after cardiac injury. As for Kit + cells, genetic-lineage-tracing studies showed that Kit-Cre labels a substantial number of endothelial cells in the normal heart and that those cells expand to generate more coronary endothelial cells after injury (40)(41)(42) (43), and lineage-tracing studies show that Sca1-derived cells are most endothelial cells in the normal heart (44). Our endothelial cell-tracing study suggests that these Sca1 + endothelial cells might expand after injury and that Sca1 + nonendothelial cells minimally contributed to coronary endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that under homeostatic conditions, CD45 − c-kit + cells are unlikely to give rise to cardiomyocytes, without any detectable differences between wild type or Kit +/MCM c-kit + cells, in line with published genetic lineage-tracing studies. 10, 20, 21 …”
Section: Resultsmentioning
confidence: 99%